DNA Sequence Variations of Alleles at Two Chicken Microsatellite Loci of MCW0216 and LEI0234 - Mei-Qing, Wei; Sheng-Cheng, Zeng; Yan-Ming, Wei; Han Jianlin (Science Alert, 2011)
To verify the quality of genotyping data and understand the property of microsatellite markers to elucidate chicken genetic diversity, the DNA sequence variations of major alleles at two chicken microsatellites of MCW0216 and LEI0234 were assessed through direct sequencing of the PCR products of 26 selected chicken blood samples. The results of MCW0216 locus were interesting and useful because they showed very complicated DNA sequence structures within both flanking and repeat regions which validated alleles that were different from each other by single nucleotides. The three SNPs present within both primer regions for genotyping the MCW0216 locus called for an action to re-design new genotyping primers to avoid allelic drop-out during genotyping exercises. The LEI0234 locus was a complex of either perfect or compound tetra-nucleotide microsatellite carrying small-sized alleles with 7 to 18 perfect CTTT repeat units while all big alleles longer than 275 bp consisted of more than 20 basic CTTT repeats being interrupted by a few CCTT motifs as a stabilizing effecter contributing to the expansion of microsatellite length and allelic polymorphism. The presence of many cryptic alleles that were identical in fragment sizes but different in either flanking sequences or repeat unit compositions at both loci further warranted an intensive DNA sequence characterization of major alleles for a correct interpretation of microsatellite data.